Bio-ecology of the Tabanio coastal forest, South Kalimantan: A literature review - Fajeriadi, Hery; Dharmono, Dharmono; Mahrudin, Mahrudin; Riefani, Maulana Khalid; Arisandi, Riza; Nugroho, Bimo Aji; Suga, Nur Abdi; Fadil, Muhammad Rio (Biological Environment and Pollution, 2024)
Bio-ecology research is essential to support ecosystem conservation and management, such as that conducted in the coastal forest of Tabanio, South Kalimantan. This forest has high biodiversity and serves an important function in coastal ecosystems. However, published bio-ecology research is still small and fragmentary. This research aims to conduct a comprehensive literature review on the extent of bio-ecology recording of the Tabanio coastal forest. The method used was the PRISMA model to review relevant literature. The results found 73 documents with the keyword <bio-ekologi “hutan pantai” “Tabanio” Kalimantan Selatan> and 22 documents with the keyword <bio-ecology of "coastal forest" "Tabanio" south Kalimantan> Google Scholar.  One of them was also indexed in Scopus. After reviewing, six documents were found that were published about bio-ecology. In contrast, most of them were published in the form of derivative studies, namely the development of educational tools based on local potential. Others are stored in the campus repository. Most studies examined flora biodiversity and population structure; some were fauna studies. However, although there are various related studies, more in-depth studies on ecosystem dynamics and species interactions are still needed. This further research is needed to provide the basis for more effective and sustainable conservation and ecosystem management efforts in Tabanio's coastal forests.